Children's hospitalizations by sensitive conditions in primary care in the Northeast of Brazil - Ribeiro,Márcia Gabriela Costa (2019)
Abstract Objectives: to analyze the temporal evolution of hospitalizations due to sensitive conditions in primary care among children under five years of age in the Brazilian Northeast region. Methods: ecological descriptive study with hospitalizations data from the Sistema de Informações Hospitalares do Sistema Único de Saúde (Hospital Information System from the Public Health System). The admissions rates on sensitive conditions in primary care between 2004 and 2013 were calculated in two age groups: children under one year old and between one and five years of age. Results: there was a reduction of hospitalization rates in the Northeast, despite the existence of fluctuations in the analyzed period. Bahia and Sergipe presented, respectively, the highest and lowest admission rates (465.14 and220.19 per 10 thousand inhabitants). It has been shown that children under one year old are more affected by sensitive diseases in primary care, presenting a total rate of 709.08 per 10 thousand inhabitants. The main causes of hospitalizations were related to the infectious gastroenteritis group and its complications with a rate of 218.76 per 10 thousand inhabitants. Conclusions: despite the decrease of hospitalizations due to sensitive conditions in primary care, the Northeast still presents high rates compared to other States, thus, evidencing the need to qualify the services offered through professionals' qualification and the inclusion of health actions for the real necessity in the community.